2008
DOI: 10.1002/anie.200800628
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Hosomi–Sakurai Conjugate Allylation of Cyclic Unsaturated Ketoesters

Abstract: Despite impressive advances over the years, [1] there are still important transformations that lack catalytic asymmetric variants. While Lewis acid catalyzed additions of allylsilanes to carbonyl compounds [2] and acetals [3] have been well studied using catalytic, [4] as well as auxiliary-based methods to control absolute configuration, [5] to the best of our knowledge, there are no effective methods for catalyzing the asymmetric 1,4-addition of allyltrimethylsilane to unsaturated carbonyl compounds. [6] In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…[21] Firstly,avariety of metal salts combined with L 3 -PiPr 2 were tested in DCM at 35 8 8C (entries [1][2][3][4][5]. Encouraged by these results,various chiral N,N'-dioxide ligands coordinated with Ni(OTf) 2 were evaluated (entries [5][6][7][8][9][10]. Encouraged by these results,various chiral N,N'-dioxide ligands coordinated with Ni(OTf) 2 were evaluated (entries [5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Firstly,avariety of metal salts combined with L 3 -PiPr 2 were tested in DCM at 35 8 8C (entries [1][2][3][4][5]. Encouraged by these results,various chiral N,N'-dioxide ligands coordinated with Ni(OTf) 2 were evaluated (entries [5][6][7][8][9][10]. Encouraged by these results,various chiral N,N'-dioxide ligands coordinated with Ni(OTf) 2 were evaluated (entries [5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that many typical Lewis acids, except Cu(OTf) 2 ,c ould promote the reaction, among which Ni(OTf) 2 provided promising results,g iving the formal 1,4allylation product g-allyl-a-ketoester 4aa in 48 %y ield with 71 % ee (entry 5). [22] Since L 3 -RaPr 2 was superior in terms of enantioselectivity,t he efficiencies of other N,N'-dioxide ligands derived from l-ramipril were evaluated (entries [8][9][10]. Compared with L 3 -PiPr 2 ,d erived from S-pipecolinic acid, l-proline-derived L 3 -PrPr 2 and l-ramiprilbased L 3 -RaPr 2 displayed higher activities,y ielding the desired products with 85 and 86 %yields,respectively (entry 5 vs.entries 6and 7).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that many typical Lewis acids, except Cu(OTf) 2 ,c ould promote the reaction, among which Ni(OTf) 2 provided promising results,g iving the formal 1,4allylation product g-allyl-a-ketoester 4aa in 48 %y ield with 71 % ee (entry 5). Encouraged by these results,various chiral N,N'-dioxide ligands coordinated with Ni(OTf) 2 were evaluated (entries [5][6][7][8][9][10]. Compared with L 3 -PiPr 2 ,d erived from S-pipecolinic acid, l-proline-derived L 3 -PrPr 2 and l-ramiprilbased L 3 -RaPr 2 displayed higher activities,y ielding the desired products with 85 and 86 %yields,respectively (entry 5 vs.entries 6and 7).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Snapper and co-workers developed copper(II)-catalyzed enantioselective Hosomi-Sakurai conjugate silylallylation of cyclic unsaturated ketoesters (Scheme 1a). [9] Our group reported catalytic asymmetric conjugate allylation of coumarins with tetraallyltin. [10] However,o nly simple allyl reagents,w ithout substituents,were investigated in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we have achieved the first total synthesis of tricyclic sesquiterpene albaflavenone 1 in racemic form in 9 steps from 2-cyclopenten-1-one (9). The overall yield was 15% from 2-cyclopenten-1-one (9) (84% average yield per step).…”
mentioning
confidence: 92%